The Legal Vacuum and Dominance of Standard Contracts in the Banking Industry - Rohadi Rohadi; Hono Sejati; Tri Susilowati (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The legal vacuum in the regulation of standard contracts in the banking industry in Indonesia has become an increasingly pressing issue, given the rising dependence of the public on financial services. This study aims to explore various aspects related to the legal vacuum and the dominance of standard contracts, which often disadvantage consumers. By analyzing the provisions in the Consumer Protection Law and existing banking practices, this research identifies the negative consequences of regulatory ambiguities that facilitate abuse by banks. The study also discusses the efforts that need to be made by the government and the Financial Services Authority (OJK) to create a stronger and more transparent legal framework. The results indicate that tighter regulations and effective supervision can strengthen consumer bargaining power and reduce the risk of losses due to unfair terms in standard contracts. Thus, this research is expected to contribute to the development of more equitable and sustainable policies in the banking sector.